2009
DOI: 10.1016/j.jplph.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Implication of phospholipase D in response of Hordeum vulgare root to short-term potassium deprivation

Abstract: SummaryTo verify a possible implication of lipids and some other compounds such as hydrogen peroxide (H 2 O 2 ) and glyceraldehydes-3-phosphate dehydrogenase (G3PDH) in the response of Hordeum vulgare to an early potassium deprivation, plants were grown in hydroponics for 30 days with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…This increase in root growth was correlated with increased PA accumulation in roots ). Similarly, potassium deficiency also led to early accumulation of PA within 24 h of potassium deprivation in Hordeum vulgare (Hafsi et al 2009). Though, the overall total lipid content did not change, specific hydrolysis of phospholipid species was observed under K deprivation (Hafsi et al 2009).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This increase in root growth was correlated with increased PA accumulation in roots ). Similarly, potassium deficiency also led to early accumulation of PA within 24 h of potassium deprivation in Hordeum vulgare (Hafsi et al 2009). Though, the overall total lipid content did not change, specific hydrolysis of phospholipid species was observed under K deprivation (Hafsi et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, potassium deficiency also led to early accumulation of PA within 24 h of potassium deprivation in Hordeum vulgare (Hafsi et al 2009). Though, the overall total lipid content did not change, specific hydrolysis of phospholipid species was observed under K deprivation (Hafsi et al 2009). Thus, upregulation of OsGDPDs after 7 days of different nutrient deficiencies might play a role in regulating PA homeostasis within cell for controlling root growth or root hair formation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In vivo and in vitro studies in suspension-cultured rice cells, PLD was activated by H 2 O 2 and this activation involved a protein tyrosine kinase (Yamaguchi et al 2004). Hafsi et al (2009) reported that the eventual PLD activation may be the result of G3PDH inhibition by H 2 O 2 . It was also observed that stress-stimulated production of ROS (H 2 O 2 ) activates plasma membrane-associated PLD delta through an increase in the cytosolic Ca 2?…”
Section: Discussionmentioning
confidence: 99%